Origeniana Octava. Origen and the Alexandrian Tradition. Papers of the 8th International Origen Congress (Pisa, 27-31 August 2001), ed. L. Perrone - P. Bemardino - D. Marchini, voł. 1-11, Leuven 2003, University Press: Mitgeverij Peeters, ss. 1406. - Szram, Mariusz (Vox Patrum, 2004)
review